Bangladesh: Class, precarity and the politics of care - Siddiqi, Dina Mahnaz; Ashraf, Hasan M. (© 2017 Taylor and Francis., 2018)
This book chapter was published in the book name Women, Work and Care in the Asia-pacific [© 2017 by Taylor and Francis] and the definitive version is available at: http://doi.org10.4324/9781315652467 The book's website is at https://www.taylorfrancis.com/books/e/9781317313151